2021
DOI: 10.1016/j.omtn.2021.01.029
|View full text |Cite
|
Sign up to set email alerts
|

miR-140 inhibits osteosarcoma progression by impairing USP22-mediated LSD1 stabilization and promoting p21 expression

Abstract: Osteosarcoma is a bone tumor frequently diagnosed in children and young adults. Despite advances in chemotherapy and surgical resection, tumors metastasize in 30% of osteosarcoma patients. In addition, side effects caused by chemotherapeutic drugs, as well as the development of chemoresistance, highlight the need to identify the molecular mechanisms involved in the pathogenesis of osteosarcoma. We compared 65 osteosarcoma samples to their adjacent normal tissues, as well as commercially obtained osteosarcoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Liu et al. also found that miR-140 attenuated osteosarcoma progression via interference of USP22-involved lysine-specific demethylase 1 (LSD1) stabilization and elevating p21 expression ( 40 ). We also confirmed that USP22 enhanced viability and motility of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. also found that miR-140 attenuated osteosarcoma progression via interference of USP22-involved lysine-specific demethylase 1 (LSD1) stabilization and elevating p21 expression ( 40 ). We also confirmed that USP22 enhanced viability and motility of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mickymaray et al found that rhaponticin can inhibit OS growth by inhibiting the PI3K-Akt-mTOR pathway [25]. Liu et al reported that miR-140 inhibits OS development by influencing ubiquitin-specific protease 22 and promoting p21 expression [26].…”
Section: Discussionmentioning
confidence: 99%
“…LSD1 function in osteosarcomas is complex with many layers of regulation that are all disrupted when LSD1 is overexpressed. For example, in osteosarcoma LSD1 demethylates the p21 promoter, decreasing p21 expression and thus promoting cell cycle progression ( 78 ) ( Figure 2B ). USP22, an ubiquitin specific protease, stabilizes the LSD1/p21 interaction and facilitates the downregulated expression of p21.…”
Section: Lsd1 In Sarcomasmentioning
confidence: 99%